JES Enterprise Partnership / Nur Ernie Ezura Pisol... [et al.] - Pisol, Nur Ernie Ezura; Yusri, Siti Noor Syafiza; Abdul Malek, Nur Syahirah (2020)
We are producing product called Carrot Crisps as a starting business. Our carrot crisps are actually snacks that are made up from vegetables which are carrots as raw materials. This product is actually come up with two different types of packaging which contain with 70 g and 170 g of carrot crisps. Our product is actually a healthy one as it is high in nutritional value but low with sugar content which suits with someone that concern with healthy lifestyle but still want to consume snacks. For the price of each of product is been charge depending on size of the packaging. The small packet that contains with 70 g carrot crisps is RM 3 .20 while for the large packet is RM 6.20. These prices that been set are similar to the price of competitor product as we take their price as benchmark. Since we are new to the market, we believe that in the future our product managed to conquer their market share and later increase our share with best and good quality product. This business already been established since on 7th November 2014 and we manage to recruit for about 10 staff including general manager to be working with this company. The post that available here are clerk, technicians, factory workers and driver.